Examining patterns of coexistence in the Cape genus Tetraria (Cyperaceae) from a phylogenetic perspective : tracing the history of community assembly processes - Slingsby, Jasper (Department of Biological Sciences, 2017)
The coexistence of species is fundamentally important in maintaining high species diversity in a defined area, and is partly responsible for the remarkable diversity of the Cape Floristic Region. The ecological attributes that determine the community assembly processes of competitive interactions and ecological sorting are subject to phylogenetic constraint and niche conservatism, suggesting that patterns of coexistence should be phylogenetically structured. This study compares patterns of coexistence against phylogenetic and ecological divergence in the genus Tetraria (Cyperaceae), and related sedges in the tribe Schoeneae, at different spatial and phylogenetic scales in multiple communities across the Cape Fynbos Biome. The investigation is based on coexistence data inferred from plot data from 13 phytosociological studies, ecological distances based on plant functional traits, and phylogenetic distances based on a molecular phylogeny of the species in question. Species coexisting in plots are significantly less related than expected on the basis of chance, and plots of phylogenetic distance against coexistence show triangular relationships, implying coexistence between closely related species is restricted, but that coexistence levels between more distantly related species may vary greatly. Quantification of these triangular relationships was problematic due to the small sample sizes and the low power of the nonparametric tests used. The pattern is more pronounced when a closely related subset of the species was used in a separate analysis, suggesting that phylogenetic scale is important. Coexisting species are significantly more closely related at the study than at the plot scale, implying relaxation of the effects of competitive interactions at coarser spatial scales. Significant positive correlation between ecological and phylogenetic divergence implies that phylogenetic constraint and niche conservatism has a strong effect on the ecological attributes of the study species. These results provide support for the hypothesis that the patterns of coexistence among species' in the genus Tetraria, and related sedges in the tribe Schoeneae, are influenced by phylogenetic constraint and niche conservatism on ecological attributes.